Advances in Non‐Fullerene Acceptor Based Ternary Organic Solar Cells. Issue 1 (11th December 2017) - Fu, Huiting; Wang, Zhaohui; Sun, Yanming
Abstract : Ternary blend organic solar cells integrating multiple donor or acceptor materials in one photoactive layer have emerged as a promising strategy to simultaneously improve all device parameters compared with traditional binary solar cells. Recently, a large number of high‐performance non‐fullerene acceptor materials have been developed. Their preeminent advantages, such as strong light absorption ability and the tunability of optoelectronic properties, make them a compelling choice for fabricating ternary organic solar cells. Thus far, the state‐of‐the‐art efficiency of ternary blend system containing non‐fullerene acceptor has reached over 12%, and shows great potential in further improving the photovoltaic performance of the organic solar cells. In this review, we first describe the possible operation mechanisms in ternary systems and then primarily summarize the major achievements in different types of ternary systems based on non‐fullerene acceptors over the past few years. In the end, we conclude with the summary and prospects of non‐fullerene acceptor based organic ternary solar cells. Abstract : The recent emergence of high‐performance non‐fullerene acceptors provides versatility of designing novel ternary blend organic solar cells (OSCs). They could be employed as host acceptor materials or as a third component to complement the absorption spectra with two other absorbers in the ternary blend, to enhance the light‐harvesting capacity and thus to further improve the efficiencies of OSCs.